2006
DOI: 10.1128/aem.72.2.1258-1266.2006
|View full text |Cite
|
Sign up to set email alerts
|

Root-Associated Bacteria Contribute to Mineral Weathering and to Mineral Nutrition in Trees: a Budgeting Analysis

Abstract: The principal nutrient source for forest trees derives from the weathering of soil minerals which results from water circulation and from plant and microbial activity. The main objectives of this work were to quantify the respective effects of plant-and root-associated bacteria on mineral weathering and their consequences on tree seedling growth and nutrition. That is why we carried out two column experiments with a quartz-biotite substrate. The columns were planted with or without pine seedlings and inoculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(108 citation statements)
references
References 57 publications
3
105
0
Order By: Relevance
“…The elemental N is abundant in the earth's atmosphere [12] however; most of the tropical soils are deficient in available N. In ecosystems with low inputs and without any fertilization or soil amendments by humans, the nutrients available to plants come either from atmospheric inputs [3] or from biological fixation [15]. Biological nitrogen fixation (BNF) is one way of converting elemental nitrogen into plant usable form.…”
Section: Introductionmentioning
confidence: 99%
“…The elemental N is abundant in the earth's atmosphere [12] however; most of the tropical soils are deficient in available N. In ecosystems with low inputs and without any fertilization or soil amendments by humans, the nutrients available to plants come either from atmospheric inputs [3] or from biological fixation [15]. Biological nitrogen fixation (BNF) is one way of converting elemental nitrogen into plant usable form.…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have used such approaches so far. Among them, Calvaruso et al [11] tested the impact of the inoculation of Burkholderia glathei strain PML1(12), previously identified as being mineral weathering efficient in an in vitro assay, using microcosms containing pine seedlings grown in a mixture of biotite and quartz. They reported that this bacterial strain significantly enhanced the release of nutritive cations from biotite compared to non-inoculated plants, and improved the plant growth.…”
Section: The Microcosms Approach: a Requested Validation Stepmentioning
confidence: 99%
“…Interestingly, this growth promoting effect was only observed under nutrient-poor conditions, suggesting a role for this bacterial strain only when nutritive cations were in limit of concentration for the plant nutrition. To go further in the understanding of the mineral weathering process, Calvaruso et al [11] also addressed the question of the effect of combination of bacterial strains. These authors showed that the combination of different efficient mineral weathering bacteria in the same microcosm do not always result in a significant increase of mineral weathering and sometimes even reduces it compared to monoinoculation conditions.…”
Section: The Microcosms Approach: a Requested Validation Stepmentioning
confidence: 99%
“…Potassium-solubilizing microorganisms are capable of solubilizing the unavailable forms of potassium in K-bearing minerals such as mica, illite and orthoclase through production and excretion of organic acids such as citric, oxalic and tartaric acids. Organic acids can facilitate the weathering of minerals by releasing K from rocks or through the formation of metal-organic complexes by forming chelate with silicon ions to bring the K into solution (Song and Huang, 1988;Calvaruso et al, 2006;Bakker et al, 2004;van Scholl et al, 2008). Other possible hypotheses/mechanisms to mobilize the soil K reserve are due to biofilm formation on the rhizospheric mineral surfaces by certain bacterial strains (Balogh-Brunstad et al, 2008).…”
Section: Potassium Content and Its Uptakementioning
confidence: 99%